Study on invasive aspergillosis using galactomannan enzyme immunoassay and determining antifungal drug susceptibility among hospitalized patients with hematologic malignancies or candidates for organ transplantation. (October 2020) - Ardi, Pegah; Daie-Ghazvini, Roshanak; Hashemi, Seyed Jamal; Salehi, Mohammad Reza; Bakhshi, Heidar; Rafat, Zahra; Zareei, Mahdi; Getso, Muhammad; Basiri, Solmaz; Sarwestani, Hasti Kamali; Boroujeini, Zeinab Borjian; Ahmadikia, Kazem
Abstract: The incidence of invasive aspergillosis (IA) has dramatically increased during the last decade. This infection is associated with high morbidity and mortality, ranging from 30% to 70%, especially in immunocompromised patients. Delay in diagnosis and treatment is usually associated with high mortality rates. This study was aimed to assess the diagnostic value of Galactomannan EIA (GM) for early diagnosis of aspergillosis in hospitalized patients with underlying conditions. Also, the antifungal drug susceptibility profiles of causative agents were investigated. In this descriptive cross-sectional study, during the period of 18 months starting from September 2017 until February 2019, 22 bronchoalveolar lavage (BAL) and 13 biopsies from infected sinuses were obtained from a total of 150 patients suffering from different types of hematologic malignancies. All the samples were subjected to microscopic examination and fungal culture. Also, serum specimens were obtained from all patients (n = 135). 22 serum and 17 BAL specimens were tested for the GM level. Fungal identified were confirmed through the PCR-sequencing of the β-tubulin gene. The susceptibility to amphotericin B, itraconazole, voriconazole, posaconazole, ravuconazole, and caspofungin was evaluated according to the Clinical and Laboratory Standards Institute document M38-A2 (CLSI M38-A2) broth microdilution protocol. The results showed that the incident rate of IA was 23.33% and 35 patients with IA (12 proven cases and 23 probable cases) were diagnosed according to the European Organization for Research and Treatment of Cancer and Mycoses Study Group criteria. The 35 patients with IA in the current study comprised 19 men (54.29%) and 16 women (45.71%) with the median age of 42 years. AML (31.5%) was documented as the most prevalent risk factor among our subjects with IA and Aspergillus flavus (65.7%) was the most prevailing causal agent in this study. Among patients with IA, ague (71%) and cough (60%) were the most common symptoms. In the present study, a sensitivity of 94% and a specificity of 98% was reported for GM ELISA in BAL specimens. Also, a sensitivity of 58% and a specificity of 98% was reported for GM ELISA in serum samples. Among 6 tested antifungal drugs, the lowest minimum inhibitory concentration (MIC) values were observed for posaconazole and ravuconazole which showed the range of 0.008–0.0062 μ g m l and 0.031–0.125 μ g m l, respectively. The current study has demonstrated that determining the value of GM investigation in BAL and serum specimens can be promising in early diagnosis of IA, also molecular identification of the agents causing IA and their antifungal susceptibility patterns are essential issues for the targeted antifungal therapy and outcome improvement of patients with this life-threatening disease. Highlights: Invasive aspergillosis (IA) is the most common fungal infection in patients with hematologic malignancies. The value of GM antigen in BAL and serum can be promising in early diagnosis of IA. Posaconazole and ravuconazole have a superiority to amphotericin B in primary therapy of IA. In patients with hematological malignancies and IA the most common type of coinfection is bacterial. The renovation in hospitals increases the risk of IA in immunosuppressed patients.